Environmental displacement: the common ground of climate change, extraction and conservation. Issue 2 (27th April 2015) - Lunstrum, Elizabeth; Bose, Pablo; Zalik, Anna
Abstract : In this introduction to a special section on environmental displacement, we introduce the concept and ground it in seemingly distinct processes of climate change, extraction, and conservation. We understand environmental displacement as a process by which communities find the land they occupy irrevocably altered in ways that foreclose or otherwise impede possibilities for habitation or else disrupt access to resources within these spaces of life, work and socio‐cultural reproduction. Such dislocation amounts to environmental displacement on the grounds that it is justified by environmental or ecological rationales, motivated by desires to access natural resources, or else provoked by human‐induced environmental change and attempts to address it. Building from here, we make the case for why climate change and efforts to mitigate and adapt to it, extractive industries, and conservation initiatives should be analysed together as displacement inducing phenomena, as they are empirically connected in consequential ways and materialise from similar logics. We additionally lay out the contributions of the individual articles of the special issue and draw connections across them to help provide a preliminary framework for thinking through environmental displacement, including its causes, logics, and consequences, especially for vulnerable populations.